Diversity of Insects Useful Rice in Refugia Plants Around Organic Rice Fields in Ngompro Vilage, Ngawi Regency - Windriyanti , Wiwin; Mujoko, Tri; Ratri, Tesha Lutfika (Future Science)
Organic rice is produced from the agricultural production process with the concept of environmentally friendly PTT. One of the technologies that have been applied by organic farmers is Ecological Engineering or called Ecological Engineering (EE). Flowering plants or referred to as refugia plants are a form of ecological service for the restoration of rice agro-ecosystems, so that all control factors can work optimally towards sustainable agriculture. This study aims to determine the diversity, evenness, and richness of useful insects on refugia plants in organic rice fields in Ngompro Village, Ngawi Regency. This study used a survey method using direct observation, insect capture was carried out using a sweep net, a yellow sticky trap, and a pitfall trap. The results showed that natural enemies (useful insects) were insects and spiders. Natural enemies of insects were found in a total of 2796 individuals grouped into six orders, 20 families and 35 genera. Natural enemies of spiders were found in a total of 1107 individuals grouped in one order, 8 families, and 9 genera. The diversity index (H ') of insect species is 3.27 with the medium category. The diversity index for spider species is 2.04 with the medium category. The evenness index (E) of insect species was 0.92 with the stable category. Evenness index for spider species is 0.93 with stable category. The wealth index (R) of insect species is 4.28 with a high index value category. The wealth index for the type of spider is 1.14 with the category of low index value.